Draft Annual Plan 1968-69 Part-I Explanatory Memorandum Government of Tripura - Planning Commission (Planning Commission, 1968)
During the year, consumption of fertilizers is expected to increase much as a result of implementation of IAAP, HVP in the Territory. Accordingly, the following quantities of fertilizers are proposed to be distributed under the Scheme. It is also proposed to effect distribution of the same to the cultivators 'at the same rates of subsidies which were admissible during 1967-68.
Government of Tripura
Government of Tripura